1990
DOI: 10.1002/mana.19901490107
|View full text |Cite
|
Sign up to set email alerts
|

Compactification of Frames

Abstract: In a sense, this paper is a sequel to BANASCHEWSKI [l], dealing with aspects of compactification and frames that have come to the fore during the 21 years since [l] was written. A t that time, the concern was to describe the construction of compact &us-DORFF extension spaces for a given space in terms of frames, specifically as filter spaces in frames. The object of this was to explicate the lattice theoretic essence of certain familiar constructions in topology, much in the spirit of other work on frames a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 3 publications
0
56
0
Order By: Relevance
“…It turns out that the resulting category of proximity frames is concretely isomorphic to that of totally bounded uniform frames (see [7]) and that the compactifiable frames are exactly those that admit strong inclusions (see [1]). In classical topology it was found useful to generalize proximities by dropping symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…It turns out that the resulting category of proximity frames is concretely isomorphic to that of totally bounded uniform frames (see [7]) and that the compactifiable frames are exactly those that admit strong inclusions (see [1]). In classical topology it was found useful to generalize proximities by dropping symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Banaschewski [3] showed that if a frame L is regular and continuous, then it has a smallest strong inclusion ◭ on L given by a ◭ b ⇔ a ≺ b and either ↑a * or ↑b is compact, where ↑x = {t ∈ L : t x}, and a * is the pseudocomplement of a, i.e. the largest element of L whose meet with a is 0.…”
Section: Preliminariesmentioning
confidence: 99%
“…The set of all strong inclusions on a frame is in a one-to-one correspondence with the set of all compactifications of L. By a compactification of L we mean a compact regular frame M together with a dense onto map h : M → L, where a dense map h is one satisfying the condition that h(x) = 0 =⇒ x = 0. A map h is said to be codense if h(x) = e =⇒ x = e. The correspondence between strong inclusions and compactifications is described by Banaschewski [3] as follows: If ⊳ is a strong inclusion on L, we consider γL = {J : J is a strongly regular ideal of L} where an ideal J is said to be strongly regular if x ∈ J implies y ∈ J for some x ⊳ y.…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations